Optimasi Jaringan Distribusi Air Bersih Menggunakan Algoritma Genetika dan Data Spasial - Siti Rahmawati (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The optimization of clean water distribution networks is an essential issue in urban infrastructure management, particularly in developing countries where water demand increases rapidly while resources remain limited. This research proposes an optimization approach for water distribution networks using Genetic Algorithm (GA) combined with spatial data analysis in a Geographic Information System (GIS) environment. The study integrates hydraulic modeling with spatial parameters, including elevation, population density, and pipeline topology, to improve pressure balance and minimize energy consumption. The optimization process is performed using EPANET coupled with a GA-based optimization engine developed in MATLAB. The results show that the proposed method reduces total head loss by 28% and decreases pumping energy costs by 15% compared to conventional design approaches. Spatial data integration enhances the precision of network analysis and provides more realistic representation of topographic conditions. The findings demonstrate that GA combined with spatial data can effectively support decision-making for sustainable and cost-efficient water distribution planning.